2014
DOI: 10.4103/0972-5229.133939
|View full text |Cite
|
Sign up to set email alerts
|

Management of life-threatening calcium channel blocker overdose with continuous veno-venous hemodiafiltration with charcoal hemoperfusion

Abstract: Cases of calcium channel blocker overdose reported from India are few, and although rare, they are associated with high mortality. Management includes fluids, vasopressors, calcium gluconate or chloride, glucagon infusion, and hyperinsulinemia-euglycemia therapy along with some rescue therapies tried in anecdotal reports. We report here a case of life-threatening overdose of amlodipine with shock, refractory to conventional therapies. Salvage therapy with continuous veno-venous hemodiafiltration using charcoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scienti c evidence about the application of HA-280 and HA-230 cartridges in clinical settings (24,25). Previous study in which the e cacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could bene cially in uence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary in ammatory cytokines (12).…”
Section: Resultsmentioning
confidence: 99%
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scienti c evidence about the application of HA-280 and HA-230 cartridges in clinical settings (24,25). Previous study in which the e cacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could bene cially in uence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary in ammatory cytokines (12).…”
Section: Resultsmentioning
confidence: 99%
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scientific evidence about the application of HA-280 and HA-230 cartridges in clinical settings [ 26 , 27 ]. Previous study in which the efficacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could beneficially influence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary inflammatory cytokines [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scienti c evidence about the application of HA-280 and HA-230 cartridges in clinical settings (26,27). Previous study in which the e cacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could bene cially in uence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary in ammatory cytokines (12).…”
Section: Discussionmentioning
confidence: 99%